The Improvement of Neuropathy and Balance after Combination of Indonesian Diabetic and Indonesian Diabetic Foot Exercise on Diabetic Peripheral Neuropathy - Putri Dyah Utami Ryadi; Tertianto Prabowo; Irma Ruslina Defi (Indonesian Journal of Physical Medicine & Rehabilitation, 2017)
Background: Half of people with Type 2 Diabetes Mellitus (Type 2 DM) developed diabetic neuropathyat 25 years after being diagnosed and around 75% of the neuropathy were diabetic peripheral neuropathy(DPN), that associated with balance disturbance. This study aimed to know the effect of combining Indonesiandiabetic exercise (Senam Diabetes Indonesia/SDI) and Indonesian diabetic foot exercise (Senam Kaki DiabetesIndonesia/SKDI) on improvement of diabetic neuropathy and balance score in people with Type 2 diabeticperipheral neuropathy.Methods: Design study was a quasi-experimental study with pre-posttest design. The participants were Type 2DM patients aged 40-65 years old, with DPN confirmed based on Indonesian version of Diabetic NeuropathySymptom (DNS-INA) >1 or Indones ian version of Diabetic Neuropathy Exmination (DNE-INA) >3, who didnot do exercise regularly. All participants had Berg Balance Scale (BBS) score within 41-55, and the randomperipheral blood glucose within 100-250mg/dL. The BBS, DNE-INA, and DNS-INA score were evaluatedbefore and after 12 weeks of excercise.Results: There were 6 women aged 52-65 years. The mean of BBS, DNS-INA, and DNE-INA scores beforeand after intervention were 54.33±1.032 and 55.16±1.329 (p=0.025), 2.50±1.048 and 1.50±0.836 (p=0.063),3.66±1.505 and 1.33±0.816 (p=0.041), respectively.Conclusion: There were improvement of Berg Balance Score and Diabetic Neuropathy Score after thecombination of Diabetic exercises.Keywords: Berg Balance Score, diabetic neuropathy score, Indonesian Diabetic Exercise, Indonesian FootDiabetic Exercise